Słowacka proza liryzowana w polskich przekładach — modernizm czy awangarda? - Buczek, Marta (Przekłady Literatur Słowiańskich, 2024)
The article concentrates on the phenomenon of Slovak lyrical prose, which was developing in Slovak literature in the interwar period of the 20th century. The author of the article is interested in how this prose functions in Polish translations. The considerations presented in the article focus on the aspect of translating this prose into Polish, the possibilities of translation, translation problems related to the act of translating modernism and avant-garde elements. The author is interested in the changing artistic criteria of translators over time, their translation choices and transformations in translation, the final effect of the act of translation.